2022
DOI: 10.1101/2022.09.24.509304
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Where the Minor Things Are: A Pan-Eukaryotic Survey Suggests Neutral Processes May Dominate Minor Spliceosomal Intron Evolution

Abstract: Spliceosomal introns are segments of eukaryotic pre-mRNA that are removed ("spliced") during creation of mature mRNA, and are one of the defining and domain-specific features of gene structure in eukaryotes. Introns are spliced by a large, multi-subunit ribonucleoprotein machinery called the spliceosome, and most eukaryotic genomes contain two distinct sets of this machinery - the major (or U2-type) spliceosome is responsible for removal of the vast majority (usually > 99%) of introns in a given genome, wit… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 98 publications
1
0
0
Order By: Relevance
“…The vast majority of splice sites in Phaeophyceae are of the canonical GT-AG type (Figure S18C) and no signatures of minor U12 introns were identified in intronic sequences, in accordance with a previous study 120 . Consistent with this observation, an analysis of spliceosome proteins using a recent reference dataset 121 found that, with the exception of ZCRB1, none of the 12 minor spliceosome genes were present in brown algal genomes (Table S26), indicating that the minor intron spliceosomal associated machinery was lost in the Phaeophyceae.…”
Section: Brown Algal Introns and The Spliceosomesupporting
confidence: 91%
“…The vast majority of splice sites in Phaeophyceae are of the canonical GT-AG type (Figure S18C) and no signatures of minor U12 introns were identified in intronic sequences, in accordance with a previous study 120 . Consistent with this observation, an analysis of spliceosome proteins using a recent reference dataset 121 found that, with the exception of ZCRB1, none of the 12 minor spliceosome genes were present in brown algal genomes (Table S26), indicating that the minor intron spliceosomal associated machinery was lost in the Phaeophyceae.…”
Section: Brown Algal Introns and The Spliceosomesupporting
confidence: 91%